Predictive Coding and Pitch Processing in the Auditory Cortex - Kumar, Sukhbinder; Sedley, William; Nourski, Kirill V.; Kawasaki, Hiroto; Oya, Hiroyuki; Patterson, Roy D.; Howard, Matthew A.; Friston, Karl J.; Griffiths, Timothy D. (Journal of cognitive neuroscience, 2011)
In this work, we show that electrophysiological responses during pitch perception are best explained by distributed activity in a hierarchy of cortical sources and, crucially, that the effective connectivity between these sources is modulated with pitch strength. Local field potentials were recorded in two subjects from primary auditory cortex and adjacent auditory cortical areas along the axis of Heschl's gyrus (HG) while they listened to stimuli of varying pitch strength. Dynamic causal modeling was used to compare system architectures that might explain the recorded activity. The data show that representation of pitch requires an interaction between nonprimary and primary auditory cortex along HG that is consistent with the principle of predictive coding.